A day to smile life - Alain Manuel Chaple Gil (Revista Cubana de Estomatología, 2015)
Since 2013, the planet celebrates World Oral Health Day on March 20. The original date of this celebration was September 12, but it was modified because it coincided with other international commemorations, such as the Annual Congress of the International Dental Federation (FDI).